Nostradamus - Dimsdale, Oliver; Fox, Kerry; Higgins, Bryn; Vogel, Hal (Mentorn Barraclough Carey : distributor Discovery Communications, 2006)
Visiones y pruebas de un futuro espantoso que se hizo el misterio más famoso de todo el mundo.